2016
DOI: 10.1371/journal.pone.0168106
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis Was Negatively Associated with Alzheimer’s Disease: A Population-Based Case-Control Study

Abstract: Some of the prior literature investigated the potential association between rheumatoid arthritis (RA) and Alzheimer's disease (AD) because these two diseases may share similar inflammatory mechanisms. Nevertheless, to date, findings of the previous literature are still controversial, and some methodological limitations were observed in those studies. The aim of this case-control study was to investigate the relationship between prior RA and AD using a large population-based dataset. This study used the Taiwan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…However, in the present study, RA was Data are shown as n (%) for qualitative variables. The results were adjusted for age, gender, and all comorbidities RA = rheumatoid arthritis; DMARD = disease-modifying anti-rheumatic drug; cHR = crude hazard ratio; aHR = adjusted hazard ratio; CI = confidence interval negatively associated with dementia, which is consistent with the results of previous studies [8,12,23]. While it has been commonly assumed that NSAID use prohibits the onset of dementia, NSAIDs were not proven to be protective in an AD clinical trial [24].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, in the present study, RA was Data are shown as n (%) for qualitative variables. The results were adjusted for age, gender, and all comorbidities RA = rheumatoid arthritis; DMARD = disease-modifying anti-rheumatic drug; cHR = crude hazard ratio; aHR = adjusted hazard ratio; CI = confidence interval negatively associated with dementia, which is consistent with the results of previous studies [8,12,23]. While it has been commonly assumed that NSAID use prohibits the onset of dementia, NSAIDs were not proven to be protective in an AD clinical trial [24].…”
Section: Discussionsupporting
confidence: 87%
“…Uncontrolled active disease causes joint damage, disability, and decreased quality of life as well as cardiovascular and other comorbidities [11]. Many studies have been conducted to demonstrate the association between autoimmune diseases (e.g., RA) and dementia [12][13][14][15]. However, the results of the studies remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…RA population had an increased AD risk ( Chou et al, 2016 ). Kao et al (2016) performed a case-control study to evaluate the relationship between prior RA and AD using 2271 patients with AD as cases and 6813 patients without AD as controls. They found an inverse association between prior RA and AD ( Kao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“… Kao et al (2016) performed a case-control study to evaluate the relationship between prior RA and AD using 2271 patients with AD as cases and 6813 patients without AD as controls. They found an inverse association between prior RA and AD ( Kao et al, 2016 ). Ungprasert et al (2016) conducted a systematic review and meta-analysis of three cohort studies and two cross-sectional studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation